Effect of International Federation of Gynecology and Obstetrics- the Federation of Obstetric and Gynecological Societies of India Postpartum Intra Uterine Contraceptive Device initiative, India on postpartum contraceptive choices- last year and post-project one-year review in a rural medical college - Burman, Sougata Kumar; Mukherjee, Jayeeta; Deb, Soumen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The FIGO-FOGSI launched an initiative in 2015 to expand the use of PPIUCD in six centers in phase 1, including our institution. This study aimed at the evaluating the effect of this program on the postpartum contraceptive choices during the last year of the project and one year thereafter. Methods: This was a clinical study conducted in the Department of Obstetrics and Gynecology, College of Medicine and J. N. M. Hospital, Kalyani, West Bengal, India from 1 January 2018 to 31 December 2019. All antenatal women were counseled about the various methods available for postpartum contraception. Data was collected on a monthly basis and results were analyzed. Results: There was a marked reduction of the acceptance rate of PPIUCD after the withdrawal of the program, with mild variation of the user percentage of most other methods. Conclusions: Further initiation and continuation of this FIGO-FOGSI project may definitely improve the scenario of acceptance of postpartum family-planning methods in this institution. However, in the existing situation, the capacity of available human resources should be built towards achieving this, to sustain the same impact as while on the FOGSI-FIGO project.